Heparina e K3EDTA como anticoagulantes para tambaqui (Colossoma macropomum Cuvier, 1816) - Pádua, Santiago Benites De [UNESP]; Pilarski, Fabiana [UNESP]; Sakabe, Róberson [UNESP]; Dias-neto, José [UNESP]; Chagas, Edsandra Campos; Ishikawa, Márcia Mayumi (Instituto Nacional de Pesquisas da Amazônia, 2012)
The efficacy of sodium heparin and tripotassium EDTA as anticoagulant and their effect on the hematological parameters of tambaqui (Colossoma macropomum) were evaluated in this study. Ten fish weighing 384.9 ± 85.71 g and measuring 27.90 ± 2.10 cm were used for heparin 5.000 IU, heparin 100 IU and K3EDTA 10% evaluation. Clotting inhibition after 10 h, erythrogram and osmotic fragility of erythrocytes were observed. The results were submitted to variance analysis and means compared by Tukey test (P < 0.05). Heparin 5.000 IU, heparin 100 IU and K3EDTA 10% were effective in preventing coagulation for more than 10 h. However, tripotassium EDTA caused hemolysis since first moments. In erythrogram there was no difference (P > 0.05) in erythrocyte count, hematocrit, hemoglobin and MCHC. On the other hand, an increase in MCV (P < 0.05) in samples kept with K3EDTA10% was observed. This anticoagulant provoked a significant increase (P < 0.01) in the osmotic fragility of erythrocytes when compared to pure heparin, diluted heparin and the control group. Heparin as an anticoagulant is more appropriate for tambaqui since it was effective in preventing coagulation for more than 10 h, without causing hemolysis, changes on hematological parameters or osmotic fragility of erythrocytes.

Este estudo avaliou a eficácia da heparina sódica e do EDTA tripotássico como anticoagulantes e seus efeitos sobre os parâmetros hematológicos de tambaqui (Colossoma macropomum). Foram utilizados dez indivíduos de tambaqui com médias de 384,9 ± 85,71 g de peso e 27,90 ± 2,10 cm de comprimento total para avaliação da heparina 5.000 UI e 100 UI, bem como do K3EDTA 10%. Foram analisados a inibição da coagulação por 10 h, eritrograma e teste de fragilidade osmótica dos eritrócitos. Os resultados foram submetidos à análise de variância e as médias comparadas pelo teste de Tukey (P < 0,05). Heparina 5000 UI, heparina 100 UI e K3EDTA 10% foram eficazes na prevenção da coagulação por mais de 10 h, no entanto o EDTA tripotássico causou hemólise desde os primeiros momentos. No eritrograma não foi observada diferença (P > 0,05) na contagem de eritrócitos, hematócrito, taxa de hemoglobina e CHCM, no entanto, houve aumento do VCM (P < 0,05) nas amostras acondicionados com K3EDTA 10%. Este anticoagulante causou incremento (P < 0,01) na fragilidade osmótica dos eritrócitos quando comparado com a heparina pura, heparina diluída, e grupo controle. A utilização da heparina como anticoagulante é mais apropriada para tambaqui (Colossoma macropomum), visto que foi eficiente na prevenção da coagulação por mais de 10 h, sem ocasionar hemólise, ou alterações nos parâmetros hematológicos e na fragilidade osmótica dos eritrócitos.
Heparin and K3EDTA as anticoagulants for tambaqui (Colossoma macropomum Cuvier, 1816)
Keywords: blood clotting; hemolysis; osmotic fragility of erythrocytes; fish hematology; coagulação sanguínea; hemólise; fragilidade osmótica dos eritrócitos; hematologia de peixes